Getting the numbers right: revisiting woodfuel sustainability in the developing world. (27th October 2017) - Bailis, Rob; Wang, Yiting; Drigo, Rudi; Ghilardi, Adrian; Masera, Omar
Abstract: The United Nations' Sustainable Development Goals encourage a transition to 'affordable, reliable, sustainable and modern energy for all'. To be successful, the transition requires billions of people to adopt cleaner, more efficient cooking technologies that contribute to sustainability through multiple pathways: improved air quality, reduced emissions of short-lived climate pollutants, and reduced deforestation or forest degradation. However, the latter depends entirely on the extent to which people rely on 'non-renewable biomass' (NRB). This paper compares NRB estimates from 286 carbon-offset projects in 51 countries to a recently published spatial assessment of pan-tropical woodfuel demand and supply. The existing projects expect to produce offsets equivalent to ~138 MtCO2 e. However, when we apply NRB values derived from spatially explicit woodfuel demand and supply imbalances in the region of each offset project, we find that emission reductions are between 57 and 81 MtCO2 e: 41%–59% lower than expected. We suggest that project developers and financiers recalibrate their expectations of the mitigation potential of woodfuel projects. Spatial approaches like the one utilized here indicate regions where interventions are more (and less) likely to reduce deforestation or degradation: for example, in woodfuel 'hotspots' in East, West, and Southern Africa as well as South Asia, where nearly 300 million people live with acute woodfuel scarcity.